Pengaruh Variasi Campuran Bahan Bakar Oli Bekas (used oil) dan Minyak Jelantah Terhadap Unjuk Kerja Kompor (burner) - Pranata, Tri Agung; Sayuthi, Muhammad; Amani, Yasir; Faisal, F; Rizki, Muhammad Nuzan (E-Journal Universitas Malikussaleh, 2024)
As the era progresses, conventional fuel becomes more expensive This causes people to experience fuel difficulties daily cooking needs due to economic shortages. hence the used oil and used cooking oil is an alternative energy. but oil is needed special treatment so that it can be used as fuel. make an alternative stove fueled by economical used oil could be the solution. Method Experimental is a quantitative method used to determine variables independent (treatment) to the influence of the dependent variable (outcome) in the condition which is under control. The research uses three variables, namely the independent variable, fixed variable and dependent variable. which is where testing is carried out with water boiling test method. The fastest start-up time data is obtained by the material Burn used cooking oil in 5 minutes and take the longest to get oil used with a time of 6 minutes. shortest boiling time obtained used cooking oil, namely 5.28 minutes. and for thermal data efficiency for each material burn ranges from 14% to 26%. fuel consumption ranges from 0.526kg to 0.615kg. The boiling point of water is 99.93„ƒ. From the variations of the three fuels used in testing, namely used oil, used cooking oil, and used oil with mixture of used cooking oil, used cooking oil is a type of fuel the most optimal with a thermal efficiency value of 26%, fuel consumption 0.615 kg/hour. better match the blower speed to the nozzle hole.